El rol del Tribunal de Justicia de la Comunidad Andina en los 50 años de integración subregional (Tema Central) - García Brito, Gustavo (2020)
The Andean Community is a community of law with a high degree of institutionalization and legalization. This research aims to evaluate the role of the Andean Court in the establishment and consolidation of the Andean market, through the Liberation Program and the gradual harmonization of economic policies, especially regarding intellectual property. To this end, an empirical analysis matrix was developed based on the main pronouncements of that Court divided into three time blocks. Thus, this study concluded that the Andean Court has played various roles, establishing the bases of the community’s law and of the integration process itself, defining the outlines of the main mechanisms for the consolidation of the Andean market and collaborating to the harmonization of economic policies. Keywords: Regional economic integration, Andean Community, Andean Court, institutionalization, judicialization.